VIRULENCE STRUCTURE OF ERYSIPHE GRAMINIS TRITlCI IN HIMACHAL PRADESH - B. M. SINGH, T. R. SHARMA AND (Indian Phytopathology, 2002)
The virulence structure of Erysiphe graminis tritici population in several areas of Himachal Pradesh was studied using mobile nurseries of wheat lines carrying single genes for powdery mildew resistance. No virulence was trapped on resistance genes Pm2, Pm4 and Pm6. However, virulence on resistance gene MA (Michigan Amber x Cc8) was quite common in all the areas. Collectively, the powdery mildew population from different areas of Himachal Pradesh is virulent on all Pm genes used in the study. The analysis showed that several combinations of resistance genes like Pml and Pm2, Pml and Pm6, Pm2 and Pm4,. Pm2 and PmB, Pm4 and PmB, Pm4 and Pm6 and Pm7 and PmB could confer complete resistance against all the prevalent virulences. There was no definite pattern in the changes in virulence frequency at different sampling places or times.